The Fascist-Anti-Fascist Struggle in the Order Sons of Italy of Ontario, 1915-1946 - Principe, Angelo (Ontario History)

(untitled) (The Ontario Historical Society, 2014)
This article examines the struggle between fascists and anti-fascists in the Order Sons of Italy of Ontario, a struggle that began with the keynote speech delivered at the order’s founding convention in 1924, and was followed by the election of a fascist as Grand Venerable ten years later, a legal confrontation between the Grand Consul of the Order and the Ontario Lodge of Toronto (that involved the entire membership and, eventually, the Supreme Court of Ontario) and anti-Semitic legislation in the homeland. Italy’s loss in the Second World War finally brought the order’s flirtation with fascism to an end in 1946.